Congolese migrant learners' language, literacy and learning in a primary school in Cape Town - Mafandala, Mbembi Joel (School of Education, 2015)
When children whose first or home language is a minority language begin their school careers, they are commonly taught through the medium of a majority language for varying purposes, including the requirement that they be assessed in school through the medium of a recognised national language. For immigrant children and for children of immigrants, learning through the medium of a national language is part of their assimilation in to the society they are growing up in. However, often these children are taught only in this second or foreign language, and little support is offered to help them to gain sufficient competence in that language.This research studies how Congolese migrant learners in primary school encounter language, literacy and learning in poor schools in Cape Town, with what sorts of implications for their chances of schooling success? I conducted a qualitative case study observing three Congolese learners, who are still learning to read and write: Maboko and Mabele (in grade three) and Goya (in grade two), over a period of four weeks in a low status but functioning inner-city school. I draw on a sociocultural approach to literacy as contextualised social practice. This implies that children learn language and literacy through everyday interaction, therefore language and literacy should be studied as it happens in social life. I also look at the theoretical approaches to understanding language and literacy learning, such as reading theories, emergent literacy, as well as emergent biliteracy to understand the experiences of Congolese learners in South African primary schools.